THE INFLUENCE OF CORPORATE GOVERNANCE ON FIRM PROFITABILITY: A STUDY OF THE FIRMS LISTED ON INDIA’S NSE 500 - Mary Notts, Ruby; Roy, Dr. Amitava (The journal of contemporary issues in business and government, 2022)
A robust corporate governance is imperative in creating sound corporate culture of consciousness, lucidity and openness which in turn enables a company's management achieve its objectives in a way that maximizes profits. The given studyaims to empirically evaluate the association of firm profitabilitywith various corporate governance mechanisms, for firms traded on the NSE 500. The time period for our studyranges from 2013 to 2020 - using Ordinary Least Squares as the method of estimation. We used two estimates of firm profitability - Return on Assets (ROA) and Net Profit Margin (NPM). The analysis established significant favourable association between ROA and independent directors’as a proportion of the boards, total number of board meetings held, number of board committees and audit committee presence.With respect to NPM, results showed that it was significantly and favourably impacted by the proportion of non-executive directors on the boards, total number of board meetings, total number of board committees prevalent in the company and firm size. However, board size,audit committee presence and independent directors as a proportion ofaudit committees indicated a negative impact on NPM.